Determination of Neutron Spectrum at LINAC Using a Passive Single Sphere Spectrometer - Muhammad Helmi Hakim; Chomsin Sulistya Widodo; Bunawas Bunawas; Rasito Rasito (Natural B, Journal of Health and Environmental Sciences, 2016)
Neutron spectra at Linear Acceleration (LINAC) facility was needed to protect neutron radiation. The purpose of determination of neutron spectra at LINAC using Passive Single Sphere Spectrometer is getting spectra and neutron fluence from LINAC and knowing the influence of input voltage at LINAC to its spectra and neutron fluence output. Single Sphere Spectrometer (SSS) with diameters 30 cm using seven gold foil detectors was set in position a half of diameter (0, 3, 6, 9, 11, 12, 13 cm) from center of the SSS. Measurement of neutron count rate was performed by placing SSS under gantry of LINAC with SSD 100 cm in distances. Next, neutron count rate was used as input data in UMG 3.3 program to get spectra. Based on measurement, total of neutron fluence at LINAC 10 MV and 15 MV is 5,78 ´ 104 n/cm2.s ± 0,01 ´ 104and 9,44 ´ 105 n/cm2.s ± 0,22 ´ 105, so increasing input voltage at LINAC was followed by increased neutron fluence.